Fractional hedonic games - Aziz, H; Brandl, F; Brandt, F; Harrenstein, P; Olsen, M; Peters, D (Association for Computing Machinery (ACM), 2019)
The work we present in this article initiated the formal study of fractional hedonic games (FHGs), coalition formation games in which the utility of a player is the average value he ascribes to the members of his coalition. Among other settings, this covers situations in which players only distinguish between friends and non-friends and desire to be in a coalition in which the fraction of friends is maximal. FHGs thus not only constitute a natural class of succinctly representable coalition formation games but also provide an interesting framework for network clustering. We propose a number of conditions under which the core of FHGs is nonempty and provide algorithms for computing a core stable outcome. By contrast, we show that the core may be empty in other cases, and that it is computationally hard in general to decide non-emptiness of the core.